2015
DOI: 10.1016/j.alter.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Research with persons with intellectual disabilities: An inclusive adaptation of Tourangeau's model

Abstract: a b s t r a c tThis paper demonstrates how Tourangeau's model of survey response (Tourangeau, 1984) can be adapted to facilitate research with people with intellectual disabilities. As the focus on voice of marginalized people become increasingly important, especially when involving service outcomes and policy making, researchers in fields such as quality of life continue to seek sound research methods to present true voice of such persons. To achieve this, this paper consolidates challenges and strategies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
(40 reference statements)
0
10
0
2
Order By: Relevance
“…The present authors found that most problems were within the comprehension component, which is in line with the study of a newly developed patient‐reported outcome measure for thyroid patients in the general population (Watt et al, ). Jen‐Yi et al () described how Tourangeau’s () four‐stage cognitive model (comprehension, retrieval, judgement, response) can be adapted to facilitate research with PID. The present authors followed many of these adaptations when using the QAS (Willis, ): preparing participants (i.e., easy to read information letter, practice questions, emphasize that this is not an exam), enabling participants to choose the interview site and time, ordering related questions and simplifying explanations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present authors found that most problems were within the comprehension component, which is in line with the study of a newly developed patient‐reported outcome measure for thyroid patients in the general population (Watt et al, ). Jen‐Yi et al () described how Tourangeau’s () four‐stage cognitive model (comprehension, retrieval, judgement, response) can be adapted to facilitate research with PID. The present authors followed many of these adaptations when using the QAS (Willis, ): preparing participants (i.e., easy to read information letter, practice questions, emphasize that this is not an exam), enabling participants to choose the interview site and time, ordering related questions and simplifying explanations.…”
Section: Discussionmentioning
confidence: 99%
“…(Willis, ). These suggestions and rules for designing good survey questionnaires were taken into account (Floyd & Fowler, ; Jen‐Yi, Krishnasamy, & Der‐Thanq, ; Willis, ).…”
Section: Methodsmentioning
confidence: 99%
“…In the adjustment phase, co-researchers helped to apply general rules stated in the literature on informed consent, questions, easy language and settings and lay out of the questionnaire. [ 10 , 12 , 14 , 22 ]. During the reflection phase the adjusted scales and test outcomes provided clues for the in-depth discussion on further recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Also, providing high quality answers can be difficult for proxy respondents, as shown in a study by Andresen and colleagues where proxies tended to overestimate impairment and underestimate health-related quality of life [ 13 ]. Besides the challenges of proxy-administered questionnaires [ 12 ], the need to listen to the views and experiences of people with ID themselves is increasingly acknowledged [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psychology and language science publications highlight that people with mental disabilities are able to communicate and make choices about issues that directly concern them. These studies suggest practical solutions to facilitate interviews, considering the importance of the environment, duration, type of questions and even the body language of the interlocutor (Atkinson, 1988; Heal and Sigelman, 1995; Jen-Yi et al, 2015). The linguist Williams uses the conversational analysis method described by Williams and Porter (2016) to provide highly detailed descriptions of the interactions between a researcher and the person with a disability when assisted by a caregiver.…”
Section: Does the Consumer With Disabilities Play A Role In The Reseamentioning
confidence: 99%